Implementation of Surah As-Sajdah Verse 5 in Primary Education Institutions - Nur Huda (Tarbiyah Departement collaboration with AMCA, 2021)
Islamic education is actually an effort to realize the spirit of Islam, as an effort to create a life that is imbued with Islamic values. Then, with this Islamic spirit, the joints of life in society are built. The purpose of Islamic education is the formation of noble morals, preparation for the life of the world and the hereafter, cultivating a scientific spirit in lessons, preparing professional students as well as maintaining spirituality and religion. The author interprets the letter as-Sajdah verse 5, that in fact the essence of management is regularity. Everything has been arranged by Allah according to its level, however humans do not just stand idly by. Because the essence of this regular is how all people play their part in life. There are many things a person can do in his life to achieve his life goals. In the process of getting to the goal, there will be interactions among humans. The manager in an Islamic education institution is the principal of the school. The principal has the role and responsibility to plan and manage all activities in the school. The management is carried out by involving all educators and education staff, so that the learning process can be maximized. This action involves all educators and education personnel in schools, in accordance with their respective main tasks and functions. There is no easy achievement without going through the stages of management.